Pengaruh Financial Knowledge, Financial Attitude dan Locus of Control terhadap pengelolaan keuangan mahasiswa akuntansi FEB Universitas Mataram - Baiq Auliya Salsabilla; Lilil Handajani; Nurabiah nurabiah (UNIVED Press, 2023)
The goal of this research is to determine how financial knowledge, financial attitude, and locus of control affect accounting students at FEB Mataram University's financial management. The assessments were administered to 93 (ninety three) Accounting students at the University of Mataram's Faculty of Economics and Business. Quantitative data employing primary data are the sort of data utilized in this research. The variant-based SEM approach (PLS SEM) was used in this study's data processing procedure, which was carried out utilizing the SmartPLS 4.0 software program. The findings of this research suggest that locus of control, financial knowledge, and financial attitude all have an impact on how accounting students handle their finances. The outcomes of this study's findings will have an impact on the Faculty of Economics and Business by offering suggestions for new alternative courses that may be offered, particularly those that are closely connected to financial management.